Relationship between the Plasma Levels of Catecholamines and Return of Spontaneous Circulation in Patients with Out-of-Hospital Cardiac Arrest. (29th July 2021) - Ichikawa, Yumi; Sawada, Yusuke; Nakajima, Jun; Isshiki, Yuta; Fukushima, Kazunori; Aramaki, Yuto; Oshima, Kiyohiro
Abstract : Purpose . The dynamic state of epinephrine (Ep) in the plasma of patients with out-of-hospital cardiac arrest (OHCA) remains unclear. The purpose of this study was to evaluate the relationship between the plasma levels of catecholamines (such as epinephrine (Ep), norepinephrine (Nep), and dopamine) and vasopressin (antidiuretic hormone (ADH)) and the acquisition of return of spontaneous circulation (ROSC) in OHCA patients. Methods . This was a prospective, observational clinical study. Patients with OHCA transferred to our hospital between July 2014 and July 2017 were enrolled. The levels of catecholamines and ADH in the plasma were measured using blood samples immediately obtained on arrival at our hospital and before the administration of Ep. Patients in whom Ep was already administered prior to obtaining blood samples were excluded. Patients were divided into two groups: with and without ROSC, that is, ROSC (+) and ROSC (−) groups, respectively. The plasma levels of these agents and the conditions of resuscitation were compared between the two groups. Results . A total of 96 patients with OHCA were analyzed. The ROSC (+) and ROSC (−) groups included 34 and 62 patients, respectively. There were no significant differences observed between the two groups in age, cause of cardiopulmonary arrest, and prehospital resuscitation time. The plasma levels of Ep and Nep were significantly lower in the ROSC (+) group than in the ROSC (−) group. However, there were no significant differences in the plasma levels of dopamine and ADH between the two groups. Conclusion . Increased levels of Ep in the plasma may not be associated with the acquisition of ROSC in patients with OHCA.